Exploration of the Development of Innovative Assessment Methods for Learning PAI in the Framework of the Independent Curriculum and the Society 5.0 Era - Pingki Utami; Pitrawana Pitrawana; Deri Wanto; Mirzon Daheri (CV Media Inti Teknologi, 2024)
The research aims to investigate several aspects, namely: 1) How are innovative assessment methods applied in Islamic Religious Education (PAI) learning at SDN 32 Rejang Lebong? 2) How is the independent curriculum implemented in the learning context? 3) How will innovative assessment develop in the Society 5.0 era? The type of research is qualitative, with data sources coming from various types of qualitative research. The research results show that SDN 32 applies innovative assessment methods using creative instruments such as projects, experiments, and so on which are unique. Characteristics include an orientation to deep skills, support for diversity, use of technology, and flexibility in the form of projects, open exams, and oral presentations. The implementation of the Independent Curriculum is carried out by reducing the Basic Competencies in each subject, allowing teachers and students to focus more on essential competencies for continued learning at the next level. The essence of independent learning is giving freedom to teachers and students in the learning process. On the other hand, the independent curriculum for students and teachers involves special characteristics, namely the implementation of Project Based Learning together to develop soft skills and character in accordance with the Pancasila student profile. The focus is on essential material so that there is sufficient time for in-depth learning related to basic competencies, such as literacy and numeracy. Apart from that, teachers flexibility to carry out differentiated learning according to student's abilities.